Dynamics of pristine graphite and graphene at an air‐water interface. Issue 8 (16th February 2018) - Goggin, David M.; Samaniuk, Joseph R.
Abstract : We examine the dynamics and morphology of graphitic films at an air‐water interface in a Langmuir trough by varying interfacial surface coverage, by observing in situ interfacial structure, and by characterizing interfacial structure of depositions on mica substrates. In situ interfacial structure is visualized with Brewster angle microscopy and depositions of the interface are characterized with atomic force microscopy and field‐emission scanning electron microscopy. Compression/expansion curves exhibit a monotonically decreasing surface pressure between consecutive compressions, but demonstrate a "rebound" of hysteretic behavior when the interface is allowed to relax between consecutive compressions. This dynamic results from a competition between consolidation of the interface via agglomeration of particles or the stacking of graphene sheets, and a thermally‐driven relaxation where nanometer‐thick particles are able to overcome capillary interactions. These results are especially relevant to applications where functional films with controlled conductivity and transparency may be produced via liquid‐phase deposition methods. © 2018 American Institute of Chemical Engineers AIChE J, 64: 3177–3187, 2018